MEASURING ZAKAT IMPACT ON POVERTY AND WELFARE USING CIBEST MODEL - Beik, Irfan Syauqi; Arsyianti, Laily Dwi (Bank Indonesia, 2016)
This research attempts to analyze the role of productive-based zakat program in reducing poverty level of mustahik (zakat recipient) households from the perspective of material and spiritual dimensions. The study utilizes primary data which is obtained from interview through questionnaire in DKI Jakarta and Bogor Regency. 221 respondents are selected and interviewed as research samples. They are zakat beneficiaries managed by BAZIS DKI Jakarta and Dompet Dhuafa. The primary data collection was conducted on February until May 2015. CIBEST model comprising four indices is used as tool of analysis. These indices are welfare index, material poverty index, spiritual poverty index and absolute poverty index. It is found that the presence of zakat utilization program is able to increase welfare index of the mustahik by 96.8 percent. The material poverty index and absolute poverty index can also be reduced by 30.15 percent and 91.30 percent, respectively. Unpredictable result occurs on spiritual poverty index in which there is an increase of two households living under spiritual poverty. It means that these two zakat recipient households suffer weakening spiritual values despite materially better-off in the presence of zakat program.